Marginal leakage in Class V cavities pretreated with different laser energy densities - Ribeiro, C. F.; Anido, A. A.; Rauscher, F. C.; Yui, KCK; Goncalves, SED (Mary Ann Liebert, Inc., 2005)
The purpose of the present study was to evaluate in vitro the degree of marginal leakage in Class V cavities involving the cementoenamel junction. Cavities were 4 rum wide and 2 mm deep. The specimens received dentin pretreatment (37% phosphoric acid) followed by the Single Bond (3M) adhesive system application. The 40 specimens were then divided into four groups: Group I (control); Group 2 (Nd:YAG laser at 120 mJ/pulse, frequency of 10 Hz, power of 1.2 W); Group 3 (Nd:YAG laser at 140 mJ/pulse, frequency of 10 Hz, power of 1.4 W); Group 4 (Nd:YAG laser at 160 mJ/pulse, frequency of 10 Hz, power of 1.6 W). The cavities were restored with Z100 composite resin (3M) and light cured at 300-600 mW/cm(2) light intensity. Specimens were thermocycled to 500 cycles from 2-50 degrees C. After that, they were dried and sealed with nail varnish, respecting 1 mm around the restorations, and immersed in 0.5% methylene blue solution for 4 h. After this period, the teeth were rinsed, dried, sectioned, and analyzed in a stereoscopic loupe. The highest leakage scores were considered for each specimen. The results were statistically analyzed by the analysis of variance (ANOVA) Kruskal-Wallis test to the 5% level. For both the enamel and cementum, there was a decrease in marginal leakage with the application of laser energy; no significant differences were observed for Groups 2, 3, and 4. The results also showed a smaller tendency to marginal leakage on the cementum than on the enamel.